Comparison of In-vitro Penetration of Transdermal Patch Containing Pure Diclofenac Sodium and Nanoparticles as Analgesic and Anti-Inflammatory - Nurmalia, Zakaria; Hakim, Bangun; Urip, Harahap (Asian Journal of Pharmaceutical Research and Development, 2020)
Objective: Diclofenac sodium is a Non Steroid Anti Inflammatory class of drug which has a weakness in oral use in the form of irritation of the digestive tract. This study aims to make transdermal patches containing pure sodium diclofenac and nanoparticles with ethyl cellulose (EC) and polyvinyl pyrrolidone (PVP) polymers and compare in-vitro penetration using franz diffusion cells. Design: This research is an experimental research which will be calculated quantitatively percent cumulative penetration of pure diclofenac sodium and nanoparticles from the transdermal patch for 8 hours. Intervention: The variables that play a role in this research are pure diclofenac sodium and nanoparticles, both using and without enhancers Main outcome measures: In this study, the main measurement is the absorbance value of diclofenac sodium using a spectrophotometer, which penetrates the skin on franz diffusion cells and is converted to percent cumulative penetration. Result: Transdermal patches containing diclofenac sodium nanoparticles have a higher cumulative percent penetration (58.87 ± 0.7458%) than transdermal patches containing pure sodium diclofenac (46.6 ± 1.9438%), but not higher than transdermal patches containing pure sodium diclofenac with the addition of propylene glycol enhancers (67.59 ± 1.4675%). The three transdermal patch formulas did not differ significantly to the percent cumulative drug penetration (p> 0.05).Transdermal patches containing diclofenac sodium nanoparticles have a higher analgesic and anti-inflammatory effect than transdermal patches containing pure sodium diclofenac up to 480 minutes. Conclusion: Transdermal patches containing sodium diclofenac nanoparticles have been shown to be able to increase drug penetration through the rabbit’s stomach skin membrane in-vitro using Franz diffusion cells. Transdermal patches of pure diclofenac sodium and nanoparticles provided analgesic and anti-inflammatory effects that were significantly different from negative control.